Chronic Exposure to Dim Light at Night or Irregular Lighting Conditions Impact Circadian Behavior, Motor Coordination, and Neuronal Morphology - Delorme, Tara C.; Srikanta, Shashank B.; Fisk, Angus S.; Cloutier, Marie-Ève; Sato, Miho; Pothecary, Carina A.; Merz, Chantal; Foster, Russell G.; Brown, Steven A.; Peirson, Stuart N.; Cermakian, Nicolas; Banks, Gareth T. (Frontiers in Neuroscience, 2022)
Mistimed exposure to light has been demonstrated to negatively affect multiple aspects of physiology and behavior. Here we analyzed the effects of chronic exposure to abnormal lighting conditions in mice. We exposed mice for one year to either: a standard light/dark cycle, a “light-pollution” condition in which low levels of light were present in the dark phase of the circadian cycle (dim light at night, DLAN), or altered light cycles in which the length of the weekday and weekend light phase differed by 6 hours (“social jetlag”). Mice exhibited several circadian activity phenotypes, as well as changes in motor function, associated particularly with the DLAN condition. Our data suggest that these phenotypes might be due to changes outside the core clock. Dendritic spine changes in other brain regions raise the possibility that these phenotypes are mediated by changes in neuronal coordination outside of the clock. Given the prevalence of artificial light exposure in the modern world, further work is required to establish whether these negative effects are observed in humans as well.